Tinjauan yuridis penelantaran hak asuh anak setelah perceraian - Amaliya, Nabila Salma (Maliki Interdisciplinary Journal, 2024)
This research discusses the neglect of child custody after divorce based on the perspective of applicable law in Indonesia, by applying juridical normative research methods. The main focus of this research is the existing laws and regulations, the views of legal experts, and the principles related to child custody after divorce. The approach used is a statute approach, which analyzes various legal sources such as the Marriage Law, Child Protection Law, and Compilation of Islamic Law. This research raises issues regarding child custody, parental responsibilities after divorce, and legal protection of the rights of children who are abandoned by parents. Through this research, it is hoped that a deeper understanding of the importance of fulfilling children’s rights after divorce and the responsibility of parents in maintaining children’s welfare in terms of physical, mental and social aspects will be created.